SMAD pathway mediation of BDNF and TGFβ2 regulation of proliferation and differentiation of hippocampal granule neurons - Lu, J. (2005)
Hippocampal granule cells self-renew throughout life, whereas their cerebellar counterparts become post-mitotic during early postnatal development, suggesting that locally acting, tissue-specific factors may regulate the proliferative potential of each cell type. Confirming this, we show that conditioned medium from hippocampal cells (CMHippocampus) stimulates proliferation in cerebellar cultures and, vice versa, that mitosis in hippocampal cells is inhibited by CMCerebellum. The anti-proliferative effects of CMCerebellum were accompanied by increased expression of the cyclindependent kinase inhibitors p21 and p27, as well as markers of neuronal maturity/differentiation. CMCerebellum was found to contain peptide-like factors with distinct antiproliferative/ differentiating and neuroprotective activities with differing chromatographic properties. Preadsorption of CMCerebellum with antisera against candidate cytokines showed that TGFβ2 and BDNF could account for the major part of the anti-proliferative and pro-differentiating activities, an interpretation strengthened by studies involving treatment with purified TGFβ2 and BDNF. Interference with signaling pathways downstream of TGFβ and BDNF using dominant-negative forms of their respective receptors (TGFβ2-RII and TRKB) or of dominant-negative forms of SMAD3 and co-SMAD4 negated the antiproliferative/ differentiating actions of CMCerebellum. Treatment with CMCerebellum caused nuclear translocation of SMAD2 and SMAD4, and also transactivated a TGFβ2- responsive gene. BDNF actions were shown to depend on activation of ERK1/2 and to converge on the SMAD signaling cascade, possibly after stimulation of TGFβ2 synthesis/secretion. In conclusion, our results show that the regulation of hippocampal cell fate in vitro is regulated through an interplay between the actions of BDNF and TGFβ.